Learning Style Preference: Results of Repetitive Cross-Sectional Surveys in an Higher Education Institution - Simangunsong, Eliot (JPI (Jurnal Pendidikan Indonesia), 2020)
Using the theoretical framework of the Felder-Silverman Learning Styles Model, this study aims to understand the learning styles of middle school students entering the university to promote teaching innovation and improve the quality of the learning experience. A quantitative research method was applied through repeated cross-sectional surveys for 3 years among 2,325 students. Systematic analysis is applied to investigate respondent learning styles. Data analysis showed a significant difference in terms of the sex of students, while in terms of graduation years, the proportion of sequential students showed a significant increase from 2014 to 2016; this might imply that students from scientific or analytic backgrounds increasingly choose management schools. As expected, management students are active in character, except in accounting programs, where sensing learners are dominant. Innovative, active and visual-based learning is also preferred. Through the findings of this study, we conclude that interest in studies is related to the learning dimensions. The teaching style must follow the characteristics of the learning dimensions to provide an optimal learning experience. Here, it is important to implement an innovation-based learning process in higher education institutions.